2006
DOI: 10.1111/j.1600-051x.2006.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal healing after non‐surgical therapy with a modified sonic scaler: a controlled clinical trial

Abstract: The sonic scaler system and S/RP seem to provide similarly favourable periodontal healing results, although in deep pockets S/RP appeared to achieve a better resolution of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
29
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 64 publications
8
29
1
3
Order By: Relevance
“…However, in contrast to the present study, they did not distinguish between different pocket depth categories when comparing the BOP values. The observed superior BOP reduction in deep S/RP sites is in line with another study (Christgau et al 2006), which also reported a better BOP reduction in deep pockets with S/RP than with a sonic scaler. Kocher et al (2005) compared the efficacy of the Vector ™ system and a conventional ultrasonic scaler in periodontal maintenance therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in contrast to the present study, they did not distinguish between different pocket depth categories when comparing the BOP values. The observed superior BOP reduction in deep S/RP sites is in line with another study (Christgau et al 2006), which also reported a better BOP reduction in deep pockets with S/RP than with a sonic scaler. Kocher et al (2005) compared the efficacy of the Vector ™ system and a conventional ultrasonic scaler in periodontal maintenance therapy.…”
Section: Discussionsupporting
confidence: 91%
“…In order to facilitate subgingival debridement and to improve clinical and microbiological results, power‐driven instruments, such as sonic and ultrasonic scalers, have been proposed (AAP Position Paper 2000). Numerous studies have reported similarly favourable clinical healing outcomes following sonic, ultrasonic, and manual instrumentation (Badersten et al 1981, 1984, Loos et al 1987, 1989, Laurell & Pettersson 1988, Laurell 1990, Tunkel et al 2002, Hallmon & Rees 2003, Christgau et al 2006). However, the use of ultrasonic scalers in dentistry may bear some problems for the patients and operators (Trenter & Walmsley 2003).…”
mentioning
confidence: 99%
“…demonstrated that both these therapeutical approaches determine similar periodontal healing in terms of probing pocket depths, bleeding on probing and periodontal attachment gain (19)(20)(21)(22)(23)(24)(25), several Authors reported that there is need for less time to treat periodontal patients with the mechanical debridment method (4,25,26). Our results agree with these studies since the mean treatment time for instrumentation of two quadrants was 84.75 minutes for the mechanical versus 119.25 minutes for the manual side.…”
supporting
confidence: 88%
“…Responses to periodontal treatment of patients infected with A. actinomycetemcomitans have been investigated (6,10,39). Some previously published studies have even demonstrated that A. actinomycetemcomitans is a pathogen which is able to invade periodontal tissues but evade mechanical-chemical therapies (27,32,33).…”
mentioning
confidence: 99%